Improving Hijaiyah Letter Identification Skills through the Iqro’ Method Assisted by Hijaiyah Letter Card Media among Fourth-Grade Students with Learning Difficulties - Siti Nur Aenah; Shely Cathrin (Poltanesa, 2026)
The ability to identify Hijaiyah letters is a fundamental prerequisite for learning to read the Qur’an. However, some elementary school students continue to experience difficulties in recognizing, distinguishing, and pronouncing Hijaiyah letters correctly. This study aimed to improve the Hijaiyah letter identification ability of fourth-grade students with learning difficulties through the implementation of the Iqro’ method assisted by Hijaiyah letter card media. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. Data were collected through observation, tests, documentation, and field notes. The findings revealed a substantial improvement in students’ Hijaiyah letter identification ability across the research cycles. The average score increased from 42.5% in the pre-cycle stage to 67.5% in Cycle I and further improved to 90% in Cycle II. Improvements were also observed in student participation during the learning process, increasing from 70% in Cycle I to 90% in Cycle II. The use of the Iqro’ method combined with Hijaiyah letter card media provided concrete learning experiences that facilitated letter recognition, strengthened visual memory, and increased student engagement. These findings indicate that the integration of the Iqro’ method and Hijaiyah letter card media is effective in improving Hijaiyah letter identification skills among elementary school students with learning difficulties.